Ammonia removal from wastewater streams through membrane contactors: Experimental and theoretical analysis of operation parameters and configuration - Hasanoglu, A.; Romero, J.; Perez, B.; Plaza, A. (ELSEVIER SCIENCE SA, 2010)
Ammonia removal from water was studied through hydrophobic hollow fiber and flat sheet membrane contactors. These hydrophobic membrane contactors were used to separate the water stream to be treated and a receiving solution. A diluted solution of sulfuric acid was used as a receiving solution to accelerate the removal of ammonia by means of a reaction converting the ammonia into ammonium sulfate ((NH4)(2)SO4), which could be recovered as a by-product [1-3]. Experimental work using commercial hollow fibers under different operation configurations, temperature and hydrodynamic conditions allowed obtaining significantly high extraction percentages of ammonia up to 99.83%. A theoretical model has been developed based on a resistance-in-series model that satisfies with the data those obtained from the experiments. The mass transfer of ammonia has been described by means of both Knudsen and molecular diffusion. However, it has not found a significant difference between the results obtained from the two mechanisms indicating both transport regimes could be possible for the studied system. The circulation configuration of the solutions was found to have a strong effect on the efficiency of the process. Thus, the best circulation configuration of the solutions for the hollow fiber contactors entailed the flow of feed solution in the shellside while the receiving solution in the lumenside of the membranes. (C) 2010 Elsevier BM. All rights reserved.
Keywords: Ammonia removal; Hollow fiber; Membrane contactor; Mass transfer; HOLLOW-FIBER MEMBRANES; MASS-TRANSFER; STRIPPING PROCESS; ABSORPTION; MODULES; PVDF; Engineering